Do applicants fake their personality questionnaire responses and how successful are their attempts? A case of military pilot cadet selection - Galić, Zvonimir; Jerneić, Željko; Parmač Kovačić, Maja (2012)
This paper presents the results of three interrelated studies investigating the occurrence of response distortion on personality questionnaires within selection and the success of applicants in faking situations. In Study 1, comparison of the Big Five personality scores obtained from applicants in a military pilot cadet selection procedure with participants responding honestly, faking good, and faking an ideal candidate revealed that applicants responded more desirable than participants responding honestly but less desirable than respondents under fake instructions. The occurrence of faking within the military pilot selection process was replicated in Study 2 using the Eysenck Personality Questionnaire and another comparison group. Finally, in Study 3, comparison of personality profiles obtained in selection and fake job situations with experts' estimates indicated that participants were partially successful in faking the desirable profile.
Projekt MZOS
ENG